Mobile phone tasks impair frontal dynamic stability and increase fall risk during obstacle crossing in young men - Wang, Yong; Zhao, Ziqi; Liang, Leichao; Tang, Yunqi (Journal of biomechanics, 2025)
Falls, a major cause of accidental deaths, are often caused by obstacles, particularly among young people who may trip in over half of cases. Although mobile phone use has been linked to impaired gait and balance, its effect on dynamic stability during obstacle crossing is not well understood. This study investigates the impact of mobile phone usage on dynamic stability and fall risk during obstacle-crossing movements and compares the effects of various mobile phone tasks on obstacle-crossing performance. Seventeen healthy young men performed four obstacle-crossing tasks in random order: no mobile phone use, video browsing, text editing, or numerical computation. A motion capture system and two three-dimensional force plates recorded kinematic data and ground reaction forces. Gait spatiotemporal parameters and whole-body angular momentum were analyzed using one-way repeated-measures analysis of variance. Mobile phone use significantly reduced step width and stride speed while increasing obstacle-crossing time and leg-raising height (P < 0.05). Video browsing and numerical computation caused larger frontal-plane angular momentum ranges during the first single-support and second double-support phases than text editing (P < 0.05). Additionally, all mobile phone tasks increased in mean frontal plane external moments and free moments relative to the no-phone condition (P < 0.05). Mobile phone use impairs dynamic stability and elevates lateral fall risk during obstacle crossing, with numerical computation having the most detrimental impact.